Strategic Assessment of Challenges to Clinical Pharmacists in Pakistan and their Historical Relationship with Physicians - Khan, Majid; Riaz, Muhammad (Journal of Pharmacy Practice and Community Medicine)
This study through light on actual role of Clinical Pharmacists and their relationships with Physicians as well as challenges to Clinical Pharmacists in Pakistan. Pharmacy is a patient oriented profession and a Pharmacist should be clinically smart and strong, the relation between Physician and Pharmacist of many decades but unfortunately this area of Pharmacist is not meeting the modern challenges of clinical practice, in Pakistan Pharmacy. Strategies includes curricula modification, incorporation of “7 stars Pharmacist qualities recommended by WHO”, more focus on practical knowledge rather than theoretical, vacancies announcement, training regarding prescription and paid one year internship like other countries in order to stabilize health care team and to provide rational drugs to the patient to improve both health and wealth.
Keywords: Clinical Pharmacy; Clinical Pharmacist; Physician; Health care triangle; World Health Organization; Pakistan